2005
DOI: 10.1111/j.0022-2445.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

The economic consequences of the dissolution of cohabiting unions

Abstract: Although the economic effects of divorce have been well studied, a similar exploration of cohabitation has not been conducted. For this analysis, we use a sample from the National Longitudinal Survey of Youth (N = 2,372) documenting changes in economic well‐being at the end of a cohabiting relationship and comparing these results to a sample of divorced respondents. After dissolution, formerly cohabiting men's economic standing declines moderately, whereas formerly cohabiting women's declines much more precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 42 publications
4
96
1
1
Order By: Relevance
“…The regional differences that they find are relatively modest, but the cohort difference is large: In the recent cohort, women who have experienced the dissolution of a cohabiting union recover from the economic shock more quickly than women who have experienced the dissolution of a marriage, a finding that holds true throughout Canada. Previous studies have also found a lower impact of union dissolution on women in cohabiting unions, perhaps because of their greater labor force participation (Avellar and Smock 2005).…”
Section: Union Dissolutionmentioning
confidence: 90%
“…The regional differences that they find are relatively modest, but the cohort difference is large: In the recent cohort, women who have experienced the dissolution of a cohabiting union recover from the economic shock more quickly than women who have experienced the dissolution of a marriage, a finding that holds true throughout Canada. Previous studies have also found a lower impact of union dissolution on women in cohabiting unions, perhaps because of their greater labor force participation (Avellar and Smock 2005).…”
Section: Union Dissolutionmentioning
confidence: 90%
“…These studies revealed that previously married women experienced a significant and steeper initial decline in household adjusted income than those who were cohabiting, and this result was observed in the United States (Avellar and Smock 2005;Tach and Eads 2015), the United Kingdom (Fisher and Low 2015), the Netherlands (Manting andBouman 2006), andBelgium (de Regt, Mortelmans, andMarynissen 2013). In contrast, little or no difference was observed between previously married and cohabiting men (Fisher and Low 2015), and when such a difference existed, it was usually to the advantage of married men (de Regt, Mortelmans, and Marynissen 2013;Manting and Bouman 2006).…”
Section: The Economic Effects Of Union Dissolutionmentioning
confidence: 98%
“…These studies showed that, despite the fact that cohabiting couples usually do not have the same level of legal protection as married couples, cohabiting women experience a much less severe decline in income compared to their divorced counterparts (Avellar and Smock 2005), but that the gap separating the two groups has decreased over time (Tach and Eads 2015). Various explanations have been put forward to account for these findings, such as the different number of children that married and cohabiting women have, their differential level of participation in the labor market, their varying degree of access to government benefits and transfers, or the fact that cohabitation and marriage are becoming more alike with the diffusion and institutionalization of cohabiting unions over time.…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of US data from the National Longitudinal Survey of Youth, Avellar and Smock (2005) find that African American and Hispanic women, in particular, experience deterioration in their economic position relative to that of their male partners. In their examination of data from Statistics Canada's Longitudinal Administrative Databank, Le Bourdais and colleagues (2016) also find that dissolution, for both formal and informal unions, results in a greater negative economic impact among women than among men.…”
Section: The Economic Consequences Of Divorcementioning
confidence: 99%